2018
DOI: 10.1053/j.ajkd.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and the Risks of Kidney Failure and Death in Individuals With CKD

Abstract: Uric acid concentration is an independent risk factor for kidney failure in earlier stages of CKD and has a J-shaped relationship with all-cause mortality in CKD. Adequately powered randomized placebo-controlled trials in CKD are needed to test whether urate lowering may prove to be an effective approach to prevent complications and progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
173
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(189 citation statements)
references
References 53 publications
5
173
1
10
Order By: Relevance
“…In the present study, a J-shaped relationship was observed, but was not significant. In contrast, elevated SUA levels are associated with an increased risk of mortality in the general population [6] and in nondialyzed chronic kidney disease patients [7][8][9]. These results are in contrast to previous findings obtained in the general population and suggest that higher UA levels are protective against mortality in dialysis patients.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In the present study, a J-shaped relationship was observed, but was not significant. In contrast, elevated SUA levels are associated with an increased risk of mortality in the general population [6] and in nondialyzed chronic kidney disease patients [7][8][9]. These results are in contrast to previous findings obtained in the general population and suggest that higher UA levels are protective against mortality in dialysis patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Elevated levels of serum UA (SUA) are associated with an increased risk of mortality in the general population [6] and in nondialyzed chronic kidney disease patients [7][8][9]. Few studies have examined UA as a predictor of outcomes in HD patients, and controversy surrounds whether SUA is an independent risk factor for mortality in patients receiving HD [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Studies have suggested a positive association between hyperuricemia and progression of disease in individuals with renal insufficiency, including chronic kidney disease (CKD) and unrecovered allograft kidney. [5][6][7][8][9][10] Elevated serum UA is associated with abnormal endothelial function, mitochondria dysfunction and glomerular arteriolopathy and also could result in the formation of urate crystals in the nephron collecting ducts with tubular obstruction and then cause the damage of kidney structure progressively. 11 Available UA-lowering agents include the xanthine oxidase inhibitors such as febuxostat, allopurinol and benzbromarone.…”
Section: What Is Ne W and Objec Tivementioning
confidence: 99%
“…Moreover, it is also associated with major related comorbidities including, chronic kidney disease (CKD), cardiovascular disease, hypertension, diabetes, and metabolic syndrome [2,4*,7,8]. Thus, a J-shaped association between serum uric acid and all-cause mortality among patients with CKD [9], and a J-shaped association with the risk of CKD, has been shown [10]. …”
Section: Introductionmentioning
confidence: 99%